Pintar IPA tanpa bimbel SMP VII, VIII, IX / Yuni Puspita Sari, Zain Muhari Rahman ; penyunting Anisa Budi P, Retno W, Ayu WS - YUNI PUSPITA SARI; Zain Muhari Rahman; Anisa Budi P (B-First, 2015)
x, 456 hlm. : ilus. ; 18 cm.